Диалог социолога и юриста о латентной преступности, и не только об этом… - Рущенко, И. (Социология: теория, методы, маркетинг, 2001)
The article is written in form of pseudo dialogue between sociologist and lawyer. The data of interrogation of Kharkov region inhabitants in few indicators is showed in the article: 1. A part of victimized residents during last 12 months (population’s victimization proportion). 2. General quantity of reported crimes during survey. 3. Quantity of police reports. 4. Degree of latency. The so called “Latency paradox”as a world-view and as a methodological problem is discussing in the article. The author maintains the thought about necessity of developing the domestic sociology of crime in co-operation with another criminal-law disciplines.